(untitled) (Medical Forum Monthly, 2023)
Objective: To assess the outcome of intervention CDC guidelines on nurses knowledge and practices regarding aseptic techniques in operating room. Study Design: Quasi experimental study Place and Duration of Study: This study was conducted at the Bahawal Victoria Hospital Bahawalpur from 1st May 2022 to 30th September 2022. Materials and Methods: Forty six male and female nurses working in the operating room, having experience in operating room more than six months and 25-50 years of age were included. Data for the current study was collected using a validated questionnaire consisting of three sections (1. socio-demographic profile, 2. Knowledge of nurses, 3. Practices of nurses regarding aseptic techniques). The nurses were given three-month intervention education regarding CDC guidelines knowledge and practices. The duration of each session ranged between 30-45 minutes per week. Each session was started from giving the brief summary of each topic to be studied and explaining the next session. After the completion of16 weeks intervention, post interventional assessment test was be conducted through the same questionnaire to see the effect of intervention plan on knowledge and practices of nurses regarding CDC guidelines. Results: Thirty two (69.6%) were between the age group 25-35 years and 14(30.4%) were in the age between 36-50 years. Majority of the participants were females 41 (89.1%). 60.9% of the participants had diploma nursing, 30.4% did BSN while 8.7% did Post RN. The Mean experience was 6.26±3.01 years. Conclusion: The educational intervention has significant impact on the nurse’s knowledge and practice of aseptic technique. In order to improve the standard of nursing care in this area, hospital management must implement education and training initiatives to increase knowledge of SSI prevention.